Creep Characteristics and Fracture Mechanisms of a Ni‐Based Superalloy with δ Phases at Intermediate Temperatures. Issue 8 (26th May 2020) - He, Dao-Guang; Lin, Y. C.; Yin, Liang-Xing
Abstract : The creep and fracture characteristics of a Ni‐based superalloy with preprecipitated δ phases are researched at the intermediate temperatures (630–670 °C). The influences of external stress and temperature on the creep properties and rupture mechanisms are analyzed. It is observed that the creep rupture time decreases, whereas the minimum creep rate increases, as the creep temperature or external stress is raised. With raising the external stress, the failure pattern changes from the mixed intergranular/transgranular mode to the intergranular fracture. A Monkman–Grant (MG) model is established to characterize the relationship between the residual creep life and experimental parameters (external stress and temperature). The small error between the forecasted and measured residual creep life verifies that the established MG model can be applied to evaluate the creep life of the studied superalloy. Abstract : Creep and fracture characteristics of a Ni‐based superalloy with preprecipitated δ phases are researched. It is observed that the creep properties and rupture mechanisms are sensitive to external stress and temperature. A Monkman–Grant model is modified to describe the relationship between the residual creep life and external stress/temperature.